Folate – a scoping review for Nordic Nutrition Recommendations 2023 - Anne-Lise Bjørke-Monsen; Per Magne Ueland (Food & Nutrition Research, 2023)
Folate is an essential micronutrient for normal development and metabolic function, and folate deficiency is associated with an increased risk of cancer, cardiovascular disease, mental dysfuntion and negative pregnancy outcomes. When estimating folate requirements, one must consider different bioavailability and functionality between synthetic folic acid and dietary folate, together with increased needs of folate in women of fertile age, pregnant and lactating women, preterm and small for gestational age weight infants and individuals who are homozygote for the 5,10-methylenetetrahydrofolate reductase (MTHFR) gene polymorphism. In order to achieve an adequate metabolic status based on the metabolic marker total homocysteine, and not merely the absence of clinical signs of folate deficiency, the recommended intake of folate differs according to age, pregnancy and lactation. According to the World Health Organization, a decision limit for folate deficiency in adults is serum folate level below 10 nmol/L, and in women of fertile age a red blood cell folate level below 906 nmol/L in order to prevent neural tube defects. Qualified systematic reviews along with identified relevant literature have been used for this scoping review prepared for the Nordic Nutrition Recommendations 2023.